2005
DOI: 10.1063/1.1867313
|View full text |Cite
|
Sign up to set email alerts
|

Photon-stimulated recombination of self-trapped holes with electrons in pre-irradiated solid Ar

Abstract: Spatially separated stable charge centers -trapped electrons and self-trapped holes -are generated in Ar cryocrystals by a low-energy electron beam. A combination of the cathodoluminescence and photon-stimulated luminescence methods has been used to probe recombination reactions. Photon-stimulated vacuum ultraviolet intrinsic recombination luminescence from pre-irradiated solid Ar was detected for the first time. The 1.96 eV laser light has been demonstrated to release electrons from their traps that gives ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Therefore, thermo-or photostimulated electrons leave the traps and initiate neutralization reactions. It was shown that such electrons are responsible for luminescence observed in cryocrystals [39,41]. We suggest similar processes were observed in cryocondensates [42][43][44] and impurity nanoclusters [23] at temperatures below 10 K when the atoms are still immobile in solids.…”
Section: "Cold" and "Hot" Thermoluminescence Spectra From Ihcsmentioning
confidence: 62%
“…Therefore, thermo-or photostimulated electrons leave the traps and initiate neutralization reactions. It was shown that such electrons are responsible for luminescence observed in cryocrystals [39,41]. We suggest similar processes were observed in cryocondensates [42][43][44] and impurity nanoclusters [23] at temperatures below 10 K when the atoms are still immobile in solids.…”
Section: "Cold" and "Hot" Thermoluminescence Spectra From Ihcsmentioning
confidence: 62%
“…The first results demonstrating reliability of this mechanism are presented in [14]. The experiments on stimulation of relaxation processes by laser light [2,15] provide an additional proof of the mechanisms discussed.…”
Section: Methodsmentioning
confidence: 84%
“…Electrons in the conduction band have several possibilities: to escape the sample directly [5,6,9,10], or to recombine radiatively with positively charged centers [6,10,13]. The reaction of intrinsic recombination can lead to the desorption of neutral atoms [5,6].…”
Section: Activation Spectroscopymentioning
confidence: 99%
“…There are only a few publications dedicated to PSEE [5,10,12] and to the intrinsic VUV recombination luminescence caused by an external photon source [13].…”
mentioning
confidence: 99%